Pengembangan Produk Teh Cascara Herbal Celup di Koperasi Wanita Muslimat Al-Ikhlas Desa Sidomulyo - Suwasono, Sony; Kuswardhani, Nita; Nalurita, Indah; Rahmawati, Elis (Insan Kreasi Media, 2023)
Community Service (PkM) aims to process coffee skin waste into cascara herbal dipping products in order to maximize the potential of previously unutilized coffee skin waste. The method used is Participatory Action Research (PAR). The partner in this PkM is the Al-Ikhlas Muslimat Women's Cooperative which is located in Sidomulyo Village, Jember Regency. The results that have been achieved in this Community Service activity are the production of herbal cascara tea products made from coffee skin waste with the addition of ginger. Herbal cascara tea products have a distinctive taste and aroma of coffee mixed with a refreshing sour and spicy taste from the addition of ginger. The taste of the cascara herbal dipped product is a distinctive taste. Cascara herbal tea will later be packaged using primary dip bag packaging and secondary standing pouch packaging. Processing coffee skin waste provides new variations for the products produced, namely the Muslimat Al-Ikhlas Women's Cooperative in Sidomulyo Village.